1988
DOI: 10.1111/j.1365-2265.1988.tb03680.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Reproductive Dysfunction in Men With Obstructive Sleep Apnoea

Abstract: A central, reversible decrease in male sexual function appears related to some aspect of obstructive sleep apnoea (OSA). Lower serum testosterone (T) levels were documented in 15 men with OSA versus nine snorers (no OSA), (9.18 +/- 0.92 vs 11.55 +/- 0.90 nmol/l, mean +/- SEM), P less than 0.05 in a consecutive case series of 24 men referred for diagnostic overnight sleep studies. Gonadotrophins did not differ between the two groups. Although the men with OSA did not differ in body mass index (BMI) or weight fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
1
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 31 publications
10
81
1
4
Order By: Relevance
“…Men with obstructive sleep apnoea were more likely to be hypogonadal than BMI matched controls (Santamaria et al, 1988). Lower testosterone levels but similar gonadotrophin levels were found in the obstructive sleep apnoea patients, suggesting a hypothalamic-pituitary aetiology, possibly related to hypoxia, sleep fragmentation or obesity.…”
Section: Respiratory Diseasementioning
confidence: 71%
“…Men with obstructive sleep apnoea were more likely to be hypogonadal than BMI matched controls (Santamaria et al, 1988). Lower testosterone levels but similar gonadotrophin levels were found in the obstructive sleep apnoea patients, suggesting a hypothalamic-pituitary aetiology, possibly related to hypoxia, sleep fragmentation or obesity.…”
Section: Respiratory Diseasementioning
confidence: 71%
“…Other studies have demonstrated no change in upper airway caliber with high-dose testosterone [58], no development of OSA symtomatology with TRT versus placebo [91], and no effect of testosterone blockade on nocturnal breathing or chemosensitivity in OSA patients [92]. Santamarie and colleagues even demonstrated that low testosterone levels may be associated with OSA [93]. The development of OSA is likely to involve many physical and biophysiologic changes within the body.…”
Section: Obstructive Sleep Apnea Syndromementioning
confidence: 99%
“…However, in adulthood, sleep fragmentation and/or nocturnal hypoxia secondary to obstructive sleep apnea (OSA) is associated with low sex steroid levels, [3][4][5][6][7][8] which in some cases improve after correction of OSA with continuous positive airway pressure (CPAP) treatment or surgery. 3,8,9 These fi ndings raise concern that pediatric OSA, which affects 1% to 5% of children, 10 may also diminish reproductive hormone secretion during childhood, potentially interfering with normal pubertal maturation.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%